Effectiveness of Group Counseling with Live Modeling Techniques to Improve Academic Self-Efficacy of Guidance and Counseling Students - Wenny Hulukati; Idriani Idris; Ryan Hidayat Rafiola (Kuras Institute, 2022)
This research was conducted based on field phenomena in the Guidance and Counseling Department, Universitas Negeri Gorontalo. It shows that there were still students who have low academic self-efficacy abilities. The purpose of this study was to determine the effectiveness of live modeling techniques through group counseling to improve student academic self-efficacy. This study also aims to improve the academic self-efficacy of guidance and counseling students as prospective teachers and counselors. The subjects of this study were seven students as members of group counseling. The results of the research from the pre-test and post-test results obtained that tcount is greater than 23,786 < ttable 1,894, which means Ha is accepted and Ho is rejected. Hence, it was concluded that the live modeling technique in group counseling was effective in increasing the academic self-efficacy of the Guidance and Counseling students